SINKRONISASI NILAI SIRI' DALAM BUDAYA BUGIS DENGAN PRINSIP HIFZ AL-IRDH DAN KEADILAN RESTORATIF DALAM PERSPEKTIF UU NO. 1 TAHUN 2023 TENTANG KITAB UNDANG-UNDANG HUKUM PIDANA - Haq, Islamul (Institut Agama Islam Negeri (IAIN) Bone, 2023)
This study aimed to formulate a tripartite reconciliation model that synchronizes the Bugis customary value of Siri' with the principles of Islamic criminal law (Jinayah) and the positive law of Indonesia within the framework of Law No. 1 of 2023 on the Criminal Code. This research employed a normative legal research method using a statute approach and a conceptual approach, with data collected through structured library research involving primary, secondary, and tertiary legal materials. The validity of legal materials was tested through textual criticism and theoretical triangulation techniques. The findings revealed that the Siri' value in Bugis culture shared a strong philosophical convergence with the principle of Hifz al-Irdh in Islamic law, as both placed human dignity as a legally protected object. The study also confirmed that the Diyat and Afw mechanisms in Jinayah were functionally equivalent to restitution and restorative justice under the new Criminal Code, while the Tudang Sipulung deliberation tradition was structurally parallel to the Sulh mediation in Islam and restorative justice procedures under Prosecutor Regulation No. 15 of 2020. These findings established that no principled contradiction existed among the three legal systems in resolving honor-based disputes, and that their integration into a tripartite model offered the most effective and humanistic solution for criminal law enforcement in South Sulawesi. Penelitian ini bertujuan untuk merumuskan model rekonsiliasi tripartit yang mensinkronkan nilai Siri' dalam budaya Bugis dengan prinsip hukum pidana Islam (Jinayah) dan hukum positif Indonesia dalam kerangka UU No. 1 Tahun 2023 tentang Kitab Undang-Undang Hukum Pidana. Penelitian menggunakan metode penelitian hukum normatif dengan pendekatan perundang-undangan dan pendekatan konseptual, serta pengumpulan data melalui penelusuran pustaka terstruktur yang meliputi bahan hukum primer, sekunder, dan tersier. Hasil penelitian menunjukkan bahwa nilai Siri' memiliki titik temu filosofis yang kuat dengan prinsip Hifz al-Irdh dalam hukum Islam, di mana keduanya menempatkan kehormatan manusia sebagai objek hukum yang wajib dilindungi. Mekanisme Diyat dan Afw dalam jinayah terbukti setara secara fungsional dengan restitusi dan keadilan restoratif dalam KUHP Baru, sementara tradisi musyawarah Tudang Sipulung secara struktural identik dengan mediasi Sulh dalam Islam dan prosedur keadilan restoratif berdasarkan Peraturan Kejaksaan No. 15 Tahun 2020. Ketiga sistem hukum tersebut tidak memiliki pertentangan prinsipil dalam penyelesaian delik kehormatan, sehingga integrasinya dalam model tripartit merupakan solusi yang paling efektif dan berkeadilan bagi penegakan hukum pidana di Sulawesi Selatan.